Reconceptualizing Environmental Education through Indigenous Knowledge: A Community-Based Pedagogical Model from Customary Forest Practices - Muh. Arief Budiman Ramlan; Sulbadana Sulbadana; Suardi Suardi; M.Hatta Roma Tampubolon (Newinera Publisher, 2026)
This study reconceptualizes environmental education by examining customary forest governance as a community based pedagogical ecology. While environmental education is often framed within formal schooling and curriculum reform, indigenous communities have long sustained ecological knowledge through lived practice, moral guidance, and intergenerational transmission. Drawing on qualitative case study research in a customary forest community in Central Sulawesi, Indonesia, this study explores how environmental learning is embedded in everyday activities, spatial zoning practices, ritual life, institutional deliberation, and livelihood routines. Data were collected through in depth interviews, participant observation, and analysis of community narratives. The findings reveal that the forest functions not only as an ecological resource but as a formative educational landscape where ecological awareness is cultivated through participation, relational ethics, and collective accountability. Customary institutions model reflective governance, rituals reinforce moral commitment to land stewardship, and livelihood practices nurture long term ecological reasoning across generations. By interpreting customary forest practices as an integrated pedagogical system, this study expands the conceptual boundaries of environmental education beyond formal institutional settings. It argues that sustainable education must recognize indigenous pedagogical ecologies as legitimate and sophisticated forms of knowledge production and moral formation. The study contributes to ongoing debates on decolonizing environmental education and highlights the importance of community-based learning in fostering ecological consciousness.